Atypical Eclampsia: Revisited - Shabista Shaikh; Himadri Bal; Swati Lal (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2024)
Obstetrics is always full of surprises and challenges. Some of these shake us up and make us hunt the literature to convince ourselves that such a thing exists and makes us wiser. Here we report a case where a 3rd gravida presented with classical features of eclampsia and HELLP syndrome at 18 weeks of gestation defying the criteria of gestational hypertension and its sequelae presenting only after 20 weeks. The pregnancy was successfully managed on recommended guidelines. Review of literature confirmed the not so common presentation of eclampsia at such early gestation when it is designated as atypical eclampsia. The atypicality may be in the form of gestational age of presentation or clinical features that do not adhere to the classical definition of pre-eclampsia/eclampsia. The purpose of this case report is to make ourselves aware of the entity of atypical eclampsia that will enable us to zero down on the diagnosis at the right time and plan subsequent management.